Factors influencing Postoperative Sore Throat in Patients Undergoing Elective Surgeries under General Anaesthesia - Jethva Khyati C. , Agrawal Kanika , Vyas Ashutosh M , Ghumaliya Disha S. , Prajapati Apeksha S , Ninama Vijay M (South Eastern European Journal of Public Health, 2025)
Background: Sore throat (POST) is a common complication following general anesthesia, causing significant discomfort and dissatisfaction among patients. This study aimed to evaluate the incidence of POST and its potential correlations with various factors in patients undergoing elective surgeries under general anesthesia. Materials and Methods: A prospective, observational study was carried out on 60 patients (27 males, 33 females) aged 18-65 years, ASA I-III posted for elective surgeries under general anesthesia. The incidence and severity of POST along with other complications were observed at 1, 6 and 12 hours post-operatively. We also assessed for any correlation of POST with age, sex, number of intubation attempts, changes in endotracheal tube (ET) cuff pressure and duration of surgery. Results: The overall incidence of POST was 66.67%. The incidence was observed highest in 31-40 years age group, with females being more susceptible. Surgeries lasting ≥120 minutes had high incidence of POST (60%). Changes in ET cuff pressure were required in 86.67% of patients. We had reported other complications like cough (3.33%), discomfort (16.67%), and hoarseness (5.00%). No significant association was found between the grade of sore throat and the post-operative interval (χ2 = 3.096, p = 0.796). Conclusion: POST is a frequent complication following general anesthesia. Age, sex, duration of surgery, intubation attempts and changes in endotracheal tube cuff pressure are being significant influencing factors. Regular monitoring, adjustment of cuff pressure and implementation of preventive strategies may help to lower the incidence and severity of POST and thus it helps in improving patient outcomes and satisfaction.